ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN CYBER BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 - Sona Sugianto; M. Rohim; Ali Munip (PT. Hasba Edukasi Mandiri, 2025)
The development of information and communication technology in the digital era has given rise to various new types of crimes, one of which is cyberviolence targeting children. Children, as a vulnerable group, often experience online bullying, harassment, exploitation, and various other forms of non-physical violence through digital platforms. This situation raises legal questions about the extent to which national legal systems can provide adequate protection for child victims of cyberviolence. This study aims to evaluate legal protection for children who are victims of cyberviolence based on Law Number 35 of 2014 concerning Child Protection. The method applied in this study is normative legal research using a legislative approach and a conceptual approach. The legal sources used include primary sources in the form of legislation, secondary sources such as books, academic journals, and relevant research results, and tertiary sources as supporting sources. The research findings reveal that Law Number 35 of 2014 has provided a normative basis for protecting children from all forms of violence, but does not explicitly regulate cyberviolence against childrenThis results in legal protection for child victims of cyberviolence still facing challenges in terms of legal certainty and effective law enforcement. Therefore, this study emphasizes the need to strengthen and align child protection legal norms with information technology regulations to ensure more comprehensive legal protection for children in the digital era.